Adaptive fuzzy fault-tolerant control for the attitude tracking of spacecraft within finite time. (December 2021) - Gao, Shihong; Jing, Yuanwei; Dimirovski, Georgi M.; Zheng, Yan
Abstract: The problem of finite-time attitude-tracking control (ATC) for a rigid spacecraft subject to inertial uncertainties, external disturbances, actuator saturations and faults is addressed. First, a fast nonsingular terminal sliding mode (FNTSM) manifold is constructed to improve robustness. Second, the fuzzy logic system (FLS) is integrated into the manifold derivative to deal with the lumped unknown function. The specific assumptions about uncertainties in most of the existing achievements are no longer needed. Combining the FNTSM and fuzzy approximation techniques, an enhanced fault-tolerant control scheme is developed. Compared to almost all finite-time ATC results based on FLS or neural network, a new Proof line is proposed to prove that the approximation errors are finite-time stable instead of asymptotically stable. Therefore, the attitude controller presented herein guarantees the real finite-time stability in a complete sense. Finally, numerical experiments are conducted to verify the effectiveness of the solution, and comparisons with related works are displayed. Highlights: Assumptions on uncertainties in the existing achievements are abolished. Finite-time stability of fuzzy approximation errors is proved via a new Proof line. Norm approximation is exploited to reduce the parameters to be estimated online. The attitude controller guarantees the finite-time stability in a complete sense.